AFIKS PEMBENTUK VERBA BAHASA TIALO - Wahidin, Sriyana; Lembah, Gazali; Kangiden, Nurhaya (BAHASANTODEA, 2017)
The formulation of this research problems are 1.) What are the types of affix and 2.) What is the meaning of affix forming verb Tialo language? This research aims to describe the type and meaning of affix verbs form Tialo language include affix, prefix,suffix,simulfiks. This research is a qualitative descriptive research. Data collection is done by: 1.) techniques refer and 2.) record technique. Analysis of data used through: 1.) tapping techniques, 2.) techniques refer engaged, competent. 3.) recording technique and 4.) record technique. The method used to analyze the data is the distribution method and the method of matching using smallest element description technique and extension technique. Based on the results of research have found affix formers verbs Tialo language yhat includes: (1) prefix: {moN-}, {noN-} and {poN}, (2) infix: {in-}, (3) suffix: {in} and {a’a}. Affix Combination: {moN-a’a} and {noN-a’a}. The meaning of the affix of the Tialo language verb forming: (1) will do the deed, (2) is doing the deed, (3) has done the deed, (4) command, (5) take action for others and (6) has finished doing deed for others.